Vjatka-taguste udmurtide rituaalne roog tšek-tšegei - Denis Kornilov (Mäetagused)
The article deals with the ritual dish chek-chegey / shesheri common among Zavyatsky Udmurts. Chek-chegey is a pastry in the form of small dough balls, which are baked for the spring holiday Akashka (in local tradition it coincides with Easter). The dish is analyzed in comparison with similar dishes of neighboring peoples (Tatars, Kryashens). Local legends about the connection of the dish chek-chegey with the Akashka ritual are given. The article contains memories of informants about the peculiarities of cooking the dish and its microlocal differences. For the first time, materials from field research conducted by the author in 2021–2022 have been introduced into scientific circulation. In addition, the author cites his childhood memories associated with this holiday treat.